Dental Fear and Anxiety Among Pediatric Patients Attending Training Dental Clinics at the University of Science and Technology, Sana'a, Yemen - Khairan, Hamzah; Al-Dalaei, Basil; Al-Hababi, Amjad; Al-Faqih, Mustafa; Al-Qadasi, Ahmed; Farid, Akram; Al-Hajj, Hassan; Sharhan, Nasser; Al-Rumaitha, Ahmed Houria Abdulmajeed; Al-Lahim, Abdul Malik; Al-Hazwara, Harith (University of Science and Technology, Sana'a, 2024)
Background: One of the major challenges in treating pediatric patients is managing dental fear and anxiety. Several factors may contribute to dental anxiety, including fear of pain, the presence of unfamiliar individuals, changes in the treatment environment, and separation from parents. Aim: This study aimed to evaluate dental fear and anxiety among pediatric patients attending training dental clinics at the University of Science and Technology, Sana'a, Yemen. Methods: A total of 200 questionnaires were distributed to the study sample. The questionnaire was divided into three sections. The first section addressed the prevalence, gender, and age of children who experienced fear or anxiety during dental treatment. The second section included questions about factors that may increase stress and fear during treatment. The third section addressed measures that may reduce children's fear and anxiety during dental treatment. Data were analyzed using SPSS version 25.0. Results: The prevalence of dental fear and anxiety was estimated to be more than 50% among pediatric patients attending training dental clinics at the University of Science and Technology, Sana'a, Yemen. Most children who experienced fear or anxiety were aged between 6 and 9 years, and the level of fear decreased with age. Dental fear and anxiety were more commonly observed among girls and were mainly associated with sharp instruments and exodontic procedures. Children's dental fear and anxiety may contribute to avoidance of dental care, which can lead to dental caries, periodontal diseases, and compromised oral health. Conclusion: Dental fear, anxiety, and phobia are common problems affecting pediatric patients and, to some extent, adults. These problems may lead to avoidance of dental care, resulting in severe caries and periodontal diseases that negatively affect general well-being and oral health. Keywords: Oral health; dental treatment; fear response; dental visit; dental anxiety.